2022
DOI: 10.1002/2211-5463.13533
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of HMGB1 promotes vascular dysfunction in the soft palate of patients with obstructive sleep apnea via the TLR4/NF‐κB/VEGF pathway

Abstract: Obstructive sleep apnea (OSA) is characterized by the collapse of the soft palate in the upper airway, resulting in chronic intermittent hypoxia during sleep. Therefore, an understanding of the molecular mechanisms underlying pathophysiological dysfunction of the soft palate in OSA is necessary for the development of new therapeutic strategies. In the present study, we observed that high mobility group protein box 1 (HMGB1) was released by a large infiltration of macrophages in the soft palate of OSA patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Craniofacial abnormalities, such as excessive or elongated soft palate tissue, are a common contributing factor to upper airway stenosis in OSA 49 . Su et al 50 discovered a noteworthy increase in blood vessels in the lamina propria of the soft palate tissue of OSA patients. The study also revealed significantly higher levels of TLR4, p‐NF‐κB p65, vascular endothelial‐derived growth factor, and matrix metalloproteinase‐9 in the soft palate of OSA patients compared to controls.…”
Section: Molecular Mechanisms Between Gut Microbiome and Osamentioning
confidence: 99%
“…Craniofacial abnormalities, such as excessive or elongated soft palate tissue, are a common contributing factor to upper airway stenosis in OSA 49 . Su et al 50 discovered a noteworthy increase in blood vessels in the lamina propria of the soft palate tissue of OSA patients. The study also revealed significantly higher levels of TLR4, p‐NF‐κB p65, vascular endothelial‐derived growth factor, and matrix metalloproteinase‐9 in the soft palate of OSA patients compared to controls.…”
Section: Molecular Mechanisms Between Gut Microbiome and Osamentioning
confidence: 99%